2017
DOI: 10.1186/s12935-017-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

miR-335 negatively regulates osteosarcoma stem cell-like properties by targeting POU5F1

Abstract: BackgroundEvidence is accumulating to link cancer stem cells to the pathogenesis and progression of osteosarcoma. The aim of this study is to investigate the role of miR-335 in osteosarcoma stem cells.MethodsTumor spheroid culture and flow cytometry were applied to screen out osteosarcoma stem cells. Real-time quantitative PCR was used to detect the expression level of miR-335 in MG63, U2OS and 143B osteosarcoma stem cells. The relationship of miR-335 expression with osteosarcoma stem cells was then analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
(24 reference statements)
1
32
0
Order By: Relevance
“…Our previous study also showed that miR-335 was statistically downregulated in osteosarcoma stem cells. Moreover, overexpression of miR-335 suppressed stem cell-like characteristics by targeting POU5F1 ( 32 ). Our study indicated that miR-192-5p was significantly downregulated and USP1 was remarkably upregulated in 25 osteosarcoma samples and tow cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that miR-335 was statistically downregulated in osteosarcoma stem cells. Moreover, overexpression of miR-335 suppressed stem cell-like characteristics by targeting POU5F1 ( 32 ). Our study indicated that miR-192-5p was significantly downregulated and USP1 was remarkably upregulated in 25 osteosarcoma samples and tow cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Specific for OS, 3D culture systems with spheroids have been utilized for the past 2 decades for studying the effects of the tumor microenvironment on various aspects of OS biology and has been thoroughly summarized by De Luca et al (135). Derived from these multiple investigations and relevant to therapeutic strategies specifically for OS metastasis, OS spheroids have shed illumination on drug resistance mechanisms to conventional chemotherapeutics (136)(137)(138)(139)(140)(141)(142), the maintenance of cancer stem cells and tumor-initiating cells (139,143,144), impact of ECM stiffness and composition on metastatic phenotype (145,146), cues that promote vasculogenic mimicry (147,148), and metastasis favoring pathways including the roles of specific transcription factors (NF-κB) (149,150) and miRNAs (151). In addition, the feasibility of generating co-culture bicellular spheroids through the combination of HUVEC and MG-63 cells for the study of VEGF-mediated angiogenesis has recently been described (152).…”
Section: Scaffold-free 3d Models: Tumor Spheroidsmentioning
confidence: 99%
“…There have been two main approaches to 3D OS culture that bear striking resemblance to the methods previously described for modeling the ESFT: (i) scaffold-free spontaneous aggregation of tumor cells into miniature tumors, and (ii) OS cell culture in biomimetic scaffolds [181]. Liquid overlay involves the use of either specially coated (agar-agarose, Poly(2-hydroxyethyl methacrylate) (pHEMA)) or ultra low binding plates that promote the cancer cells sticking to each other as opposed to the substrate [182][183][184][185][186][187][188][189][190]. The hanging drop technique is widely used [191][192][193][194] and involves generating OS cell suspension droplets on the lids of tissue culture vessels, having them sediment, then flipping these lids upside down above media and allowing gravity to instigate aggregate formation and fall into the media [181].…”
Section: Modeling Osteosarcoma In the 3d Bm Environment 61 Generatinmentioning
confidence: 99%